A discrepancy between plasma glycated albumin and HbA1c levels in a patient with steroid-induced diabetes mellitus. (9th March 2016) - Iizuka, Katsumi; Kato, Takehiro; Mizuno, Masami; Takeda, Jun
Abstract : A 57-year-old man was admitted for the treatment of steroid-induced diabetes mellitus (DM). He also had interstitial pneumonia and, to treat it, 20 mg prednisolone had been started in April 2014. Although glycated haemoglobin (HbA1c) level was 7.8% (62 mmol/mol), his glycated albumin (GA) level was normal (13.9%) and the ratio of GA to HbA1c (GA:HbA1c) was lower than that of normal participants and patients with type 2 DM. Plasma GA and GA:HbA1c levels became persistently lower. In September 2015, HbA1c levels measured by HPLC and immunoprecipitation methods were almost the same (6.8% (51 mmol/mol) and 6.7% (50 mmol/mol), respectively), but GA (10.2%) and GA:HbA1c (1.6) were much lower. We report the case of a patient with DM where steroid administration may have caused a decrease in plasma GA and GA:HbA1c levels via increased albumin turnover.